Recognition of the microbial metabolite p-cresol in autism spectrum disorder: systematic review and meta-analysis - María Isabel Serrano-Tomás; Paulina Contreras-Romero; Mara Parellada; Javier Chaves-Cordero; Javier Zamora; Martha Hengst; Patricia Pozo; Rosa del Campo; Rosa del Campo; Rosa del Campo; Sheyla Guzmán-Salas (Frontiers in Molecular Neuroscience)
IntroductionIn recent years, research has focused on the gut-brain axis and its microbial metabolites as potential etiological or physiopathological agents of autism spectrum disorders (ASDs). Elevated levels of the organic compound para-cresol (p-cresol) have been reported in various populations of children with ASD, suggesting that it could be validated as a possible ASD biomarker related to microbiota. The aim of this study was to perform a systematic review of p-cresol in ASD along with a meta-analysis to elucidate the scientific evidence of its potential as a biomarker.MethodsA search was performed in the PubMed, Web of Science and Scopus databases in May 2024. The Axis critical appraisal tool was used to evaluate the methodological quality of the studies included in the review. Three independent reviewers examined the identified records and performed data extraction.ResultsThe systematic review yielded 15 articles, of which only 6 were ultimately used for the meta-analysis. Urinary p-cresol levels were significantly higher in those with ASD than in healthy controls, whereas no significant differences were observed in feces.ConclusionThis meta-analysis validates that in ASD an increased level of p-cresol is detected in urine, which could represent a marker of microbiota evolution assessment in the pathogenesis of the disease. However, further research is needed to determine whether there is a causal relationship between the role of this metabolite and the pathophysiology of ASD and to validate its clinical utility.